Financial Reporting Quality and Invest Decisions: Evidence from Listed Manufacturing Companies in Nigeria - AJAYI-OWOEYE, Ayooluwa Olotu; AKINWUNMI, Abiodun Jelil; OLAYINKA, Ifayemi Moses; PELEMO, Morayo Abimbola (Archives of Business Research, 2022)
The disparaging nature of the Nigerian capital market, investment environment and the outline of the entire economy affirms the need for investors to give ample responsiveness to the precariousness of the global economic climate before investment decisions are undertaken since the resultant effect is seen in the deceleration in domestic expansion, prompted economic instability, increased inflation rate amongst others which has affected market value of shares of firms in the economy. Therefore the study examined the effect of financial reporting quality on investment decision in Nigerian listed manufacturing companies. The study employed ex-post facto research design. The population of the study was 52 manufacturing companies listed on the Nigerian exchange as at 31st December, 2020. Ten companies were purposively chosen for the study owing to data availability and total asset base covering a sample period of 2011-2020. Descriptive and inferential (Multiple Regression) statistics were used to analyze the data. The findings revealed that financial reporting quality have a significant effect on market price per share of listed manufacturing firms in Nigeria (Adj.R2= 0.316560, F(3)= 16.28516, p<0.05).The study concluded that financial reporting quality as measured by earnings quality, timely loss recognition and accounting conservatism has significant effect on market price per share of listed manufacturing firms in Nigeria. The study has implication for investor to understand the dynamics of financial reporting quality (timely loss recognition in terms of information, accounting conservatism and earnings quality) to guide them in portfolio diversification and investment decisions.